Pengembangan Kurikulum PAI di Era Digital Pada Madrasah Tsanawiyah: Tantangan dan Solusi Implementatif - Isnaini Purba; Mutia Arisya Lubis; Rizka Suri Hadi Sangra (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to examine the process of Islamic Education (PAI) curriculum development in the digital era at Madrasah Tsanawiyah, as well as the challenges encountered and the solutions that can be implemented. The main focus is on identifying existing challenges and exploring applicable solutions. The research method employed is a literature review combined with descriptive analysis of curriculum documents and experiences of implementation in the digital era. The findings reveal that the development of the PAI curriculum faces several obstacles, including limitations in human and financial resources, limited use of technology in learning, and low stakeholder involvement in the processes of curriculum design and evaluation. In addition, issues related to students’ learning motivation and the lack of variation in instructional strategies also hinder the optimal implementation of the curriculum. The proposed solutions include continuous professional development for teachers, the integration of information and communication technology in PAI learning, enhanced collaboration among schools, parents, and the community, and the adjustment of curriculum content to ensure its relevance to contemporary needs and challenges. A responsive and adaptive PAI curriculum is expected to improve the quality of learning and to shape a generation that is religious, critical, and well-characterized in the digital era.